Physiological and Proteomic Analyses of Drought Stress Response in Holm Oak Provenances - Valero-Galvàn, José; González-Fernández, Raquel; Navarro-Cerrillo, Rafael Maria; Gil-Pelegrín, Eustaquio; Jorrín-Novo, Jesús V (Journal of Proteome Research, 2013)
Responses to drought stress by water withholding have been studied in 1 year old Holm oak (Quercus ilex subsp. ballota [Desf.] Samp.) seedlings from seven provenances from Andalusia (southern Spain). Several physiological parameters, including predawn xylem water potentials and relative water content in soil, roots, and leaves as well as maximum quantum efficiency and yield of PSII were evaluated for 28 days in both irrigated and nonirrigated seedlings. The leaf proteome map of the two provenances that show the extreme responses (Seville, GSE, is the most susceptible, while Almer??a, SSA, is the least susceptible) was obtained. Statistically significant variable spots among provenances and treatments were subjected to MALDI-TOF/TOF-MS/MS analysis for protein identification. In response to drought stress, ?12.4% of the reproducible spots varied significantly depending on the treatment and the population. These variable proteins were mainly chloroplastic and belonged to the metabolism and defense/stress functional categories. The 2-DE protein profile of nonirrigated seedlings was similar in both provenances. Physiological and proteomics data were generally in good agreement. The general trend was a decrease in protein abundance upon water withholding in both provenances, mainly in those involved in ATP synthesis and photosynthesis. This decrease, moreover, was most marked in the most susceptible population compared with the less susceptible one.
From Duplicate 2 (Physiological and Proteomic Analyses of Drought Stress Response in Holm Oak Provenances - Valero-Galván, José; González-Fernández, Raquel; Navarro-Cerrillo, Rafael Maria; Gil-Pelegrín, Eustaquio; Jorrín-Novo, Jesús V)
Keywords: Analysis of Variance; biomass; Chlorophyll ﬂuorescence; drought stress in Holm oak; Droughts; Electrophoresis; Gel; Gene Expression Regulation; Holm oak proteomics; Physiological; Physiological: genetics; Physiological: physiology; Plant; Plant Leaves; Plant Leaves: genetics; Plant Leaves: metabolism; Plant Proteins; Plant Proteins: metabolism; Plant: genetics; Plant: physiology; Proteomics; Proteomics: methods; Quercus; Quercus ilex; Quercus: genetics; Quercus: metabolism; Quercus: physiology; Seedling; Seedling: growth & development; Seedling: metabolism; Spain; Stress; Tandem mass spectrometry; Two-Dimensional; water potential

Studies of variability in Holm oak (Quercus ilex subsp. ballota [Desf.] Samp.) through acorn protein profile analysis. - Valero Galván, José; Valledor, Luis; Navarro Cerrillo, Rafael M; Gil Pelegrín, Eustaquio; Jorrín-Novo, Jesús V (Journal of proteomics, 2011)
Studies of variability in Holm oak (Quercus ilex subsp. ballota [Desf.] Samp.), the dominant tree species in the typical Mediterranean forest, have been carried out by using electrophoresis-based proteomic analysis of acorns. Ten populations distributed throughout the Andalusia region have been surveyed. Acorns were sampled from individual trees and proteins extracted from seed flour by using the TCA-acetone precipitation protocol. Extracts were subjected to SDS-PAGE and 2-DE for protein separation, gel images captured, spot or bands quantified, and subjected to statistical analysis (ANOVA, SOM and clustering). Variable bands or spots among populations were subjected to MALDI-TOF/TOF and LC-MS/MS for identification. The protein yield of the used protocol varied among populations, and it was in the 2.92-5.92 mg/g dry weight range. A total of 23 bands were resolved by SDS-PAGE in the 3-35 kDa Mr range, with 8 and 12, out of the total, showing respectively qualitative and quantitative statistically significant differences among populations. Data allowed grouping populations, with groups being correlated according to geographical location and climate conditions, to northern and southern, as well as the discrimination of both mesic and xeric groups. Acorn flour extracts from the most distant populations were analyzed by 2-DE, and 56 differential spots were proposed as markers of variability. Identified proteins were classified into two principal categories; storage and stress/defense protein. Besides providing the first reference map of mature acorn seeds, the use of SDS-PAGE and proteomics in characterizing natural biodiversity in forest trees will be discussed.
Keywords: Acorn proteomics; Chromatography; Electrophoresis; Gene Expression Profiling; Holm oak variability; Liquid; Mass; Matrix-Assisted Laser Desorpti; Plant Proteins; Plant Proteins: metabolism; Polyacrylamide Gel; Quercus; Quercus ilex proteomics; Quercus: genetics; Quercus: metabolism; Seeds; Seeds: chemistry; Spectrometry; Tandem mass spectrometry

The Holm Oak leaf proteome: Analytical and biological variability in the protein expression level assessed by 2-DE and protein identification tandem mass spectrometry de novo sequencing and sequence similarity searching - Jorge, Inmaculada; Navarro, Rafael M; Lenz, Christof; Ariza, David; Porras, Carlos; Jorrín, Jesús (PROTEOMICS, 2005)
As a first approach in establishing the holm oak leaf proteome, we have optimised a protocol for this plant and tissue which includes the following steps: trichloroacetic acid-acetone extraction, two-dimensional gel electrophoresis (2-DE) on pH 5 to 8 linear gradient immobilised pH gradient strips as the first dimension, and sodium dodecyl sulfate-polyacrylamide gel electrophoresis on 13% polyacrylamide gels as the second one. Proteins were detected by Coomassie staining. Gel images were recorded and digitalized, and the protein spots quantified by using a linear regression equation of protein quantity on spot volume obtained against standard proteins. Analytical variance was calculated for one-hundred protein spots from three replicate 2-DE gels of the same protein extract. Biological variance was determined for the same protein spots from independent tissue extracts corresponding to leaves from different trees, or the same tree at different orientations or sampling times during a day. Values of 26% for the analytical variance and 58.6% for the biological variance among independent trees were obtained. These values provide a quantified and statistical basis for the evaluation of protein expression changes in comparative proteomic investigations with this species. A representative set of the major proteins, covering the isoelectric point range of 5 to 8 and the relative molecular massr range of 14 to 78 kDa, were subjected to liquid chromatography-tandem mass spectrometry analysis. Due to the absence of Quercus DNA or protein sequence databases, a method based on the procedure reported by Liska and Shevchenko [1] including de novo sequencing and BLAST similarity searching against other plant species databases was used for protein identification. Out of 43 analysed spots, 35 were positively identified. The identified proteins mainly corresponded to enzymes involved in photosynthesis and energetic metabolism, with a significant number corresponding to RubisCO.
Keywords: De novo sequencing; Holm oak; Leaf proteome; Tandem mass spectrometry; Two-dimensional gel electrophoresis